Influence of Weather Parameters on the Incidence of Mustard Aphid Lipaphis erysimi (Kalt.) in Lower Shiwaliks of Himachal Pradesh, India - Bala, Jyoti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present experiment was conducted on mustard crops in the Una district of Himachal Pradesh. The population dynamics and seasonal abundance of mustard aphid, Lipaphis erysimi in relation to weather parameters were analyzed. During the study, aphid’s incidence on mustard shoots began in the first week of January while its population peaked to 30.88, 28.43 and 21.90 aphids per 10 cm shoot during 11th Standard Meteorological Week (SMW) in 2018-19 & 2019-20 and 9th SMW during 2020-21. Across the locations, Galua 1 was found to have higher incidence of aphids (36.44 aphids per 10 cm shoot) during 2018-19 followed by Basoli 1 (31.88 aphids per 10 cm shoot) during 2019-20 and Galua 1 (26.65 aphids per 10 cm shoot) during 2020-21. Also, the correlation studies revealed a strong positive correlation of L. erysimi population to mean maximum and minimum temperatures which suggested that the pest population dynamics on mustard was greatly influenced by prevailing weather. It can be concluded that L. erysimi is a major insect-pest of mustard crops in the Una district of Himachal Pradesh.